2018
DOI: 10.1158/1055-9965.epi-17-1054
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Variant Located in miR-146b Promoter Region Is Associated with Prognosis of Gastric Cancer

Abstract: SNPs in the promoter region of miRNAs have been reported to be associated with cancer prognosis. Our previous study found that miR-146b had a strong correlation with the stage classification of gastric cancer and contributed to tumor progression. The current study was aimed at investigating whether an SNP located in the promoter region of could affect the survival rate of gastric cancer. Using bioinformatics tools, we identified one SNP (rs1536309) that is located in the promoter. We genotyped this SNP site to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…We considered 10 patients with active nonatrophic chronic gastritis, 9 patients with intestinal metaplasia, 11 with dysplasia (low and high grade), and 9 patients with gastric adenocarcinoma, thus including all the lesions that define the carcinogenetic process of the intestinal variant of GC (i.e., the Correa's cascade). The expression of let-7i-5p, miR-146b-5p, and -185-5p was increased in GC samples and the early neoplastic condition (dysplasia), confirming results obtained by meta-analysis approach and in accordance to several works demonstrating the importance of these miRNAs in different tumors [ Figure 6A; (33)(34)(35)(36)(37)(38)]. Despite meta-analysis results that revealed that let-7f-5p increased, we did not confirm such an alteration in our samples.…”
Section: Mirnas Targeting the Ciita Mrna Are Up-regulated In Gcsupporting
confidence: 89%
“…We considered 10 patients with active nonatrophic chronic gastritis, 9 patients with intestinal metaplasia, 11 with dysplasia (low and high grade), and 9 patients with gastric adenocarcinoma, thus including all the lesions that define the carcinogenetic process of the intestinal variant of GC (i.e., the Correa's cascade). The expression of let-7i-5p, miR-146b-5p, and -185-5p was increased in GC samples and the early neoplastic condition (dysplasia), confirming results obtained by meta-analysis approach and in accordance to several works demonstrating the importance of these miRNAs in different tumors [ Figure 6A; (33)(34)(35)(36)(37)(38)]. Despite meta-analysis results that revealed that let-7f-5p increased, we did not confirm such an alteration in our samples.…”
Section: Mirnas Targeting the Ciita Mrna Are Up-regulated In Gcsupporting
confidence: 89%
“…Chen, Jiang, et al, 2017;L. Li, Pan, et al, 2013;Liu et al, 2012;Qi et al, 2014;Sadeghi et al, 2018;Wang et al, 2014Wang et al, , 2018Yang et al, 2019;Yin et al, 2018).…”
Section: Risk Snps In Mirna Promoters/enhancersunclassified
“…GCa patients without obvious symptoms cannot be diagnosed at an early stage but usually exhibit rapid progression, so finding biomarkers with early predictive value for guiding individualized treatment is a worldwide focus. Although clinical factors have been demonstrated as important prognostic predictors for GCa patients' survival, 2,3 germline variants inherited from parents have been deemed able to explain the survival difference among patients to a great extent 4,5 . Previous reports have indicated that genetic variants in DNA repair pathways might affect patient survival due to modifying chemotherapy efficacy 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical factors have been demonstrated as important prognostic predictors for GCa patients' survival, 2,3 germline variants inherited from parents have been deemed able to explain the survival difference among patients to a great extent. 4,5 Previous reports have indicated that genetic variants in DNA repair pathways might affect patient survival due to modifying chemotherapy efficacy. 6,7 In addition, genes known to drive the tumorigenesis, proliferation, invasiveness and metastasis ability of cancer cells (eg, nuclear factor-kappa b [NF-κB], Yes-associated protein [YAP], 8 and mammalian target of rapamycin [mTOR]) also harbor genetic variants that influence the death risk of GCa patients, as indicated by our previous work.…”
Section: Introductionmentioning
confidence: 99%